MULTI-AGENT SYSTEM MODEL FOR DYNAMIC SCHEDULING IN FLEXIBILE JOB SHOP SUBJECT TO RANDOM MACHINE BREAKDOWN - Ebufegha, Akposeiyifa; Li, Simon (Proceedings - Winter Simulation Conference, 2022)
This paper presents a model for dynamic scheduling in a smart manufacturing system that can be used in a manufacturing environment subject to random machine breakdown. We employ a multi-agent system (MAS) to schedule work on a system of machines in real-time. We propose that such a system should be less sensitive to unforeseen disruptions to the system whilst yielding good results with respect to the total flowtime for parts requested of the system. The approach employed is a completely reactive approach, and as such has the benefit of not requiring the determination of a nominal schedule. Rather, we take advantage of self-organizing nature of the MAS to guide work scheduling. To evaluate the efficacy of our proposed model, we compare its performance to that of a system using predictive-reactive scheduling to solve a furniture manufacturing problem.